Spiritual Well-Being and Fulfilment, or Exploitation by a Few Smart Ones? The Proliferation of Christian Churches in West African Immigrant Communities in Canada - Baffoe, Michael (Richtmann Publishing, 2013)
Africans are spiritual by nature and hold strong beliefs in and their reverence for a Supreme Being, Spirits and their ancestors.The need for this strong spiritual attachment is not left behind when Africans migrate to Western countries. Often, the first stepin their resettlement process is to join a religious grouping. One of such countries is Canada where there is a huge presence ofChristian churches in the West African immigrant communities. While some have their origins from the continent, others werefounded in Canada by some immigrants. Using Post-Colonial theory as basis for analysis, this paper, explores the phenomenalgrowth of these religious groupings within the West African communities in Canada, examines their backgrounds and modusoperandi. The motives for founding or participating in these church groupings were found to be spiritual needs, socio-culturaland economic considerations. Among the followers, these include the use of the churches as conduits for maintaining religiousand cultural identity, and ensuring security in foreign lands. For the leaders of these churches, the motives are about not onlyresponding to spiritual needs but facilitating status improvement and financial gains.